Nonmarine ostracods (Crustacea) from South Korea, including a description of a new species of Tanycypris Triebel (Cyprididae, Cypricercinae) - Chang, Cheon Young; Lee, Jimin; Smith, Robin J. (Zootaxa, 2012)
Preliminary surveys of brackish and freshwater habitats in the southeast and east of South Korea produced a total of fifteenspecies. Ten of these species are new records for Korea, and one additional species, belonging to the genus Tanycypris, isnewly described herein. Twenty-seven species of nonmarine ostracods are now reported from Korea, but this is probablyonly a small proportion of the actual number of species inhabiting the peninsula. The presence of Dolerocypris ikeyaiSmith & Kamiya, 2006, Cryptocandona brehmi (Klie, 1934), Cryptocandona tsukagoshii Smith, 2011, Physocypria nip-ponica Okubo, 1990 and Vestalenula cylindrica (Straub, 1952) on the Korean Peninsula demonstrates that these species are also distributed on the continent, and are not endemic to Japan.